2021
DOI: 10.1055/s-0040-1721627
|View full text |Cite
|
Sign up to set email alerts
|

The Immature Granulocyte Count Is a New Predictor of the 30-Day Mortality in Intracerebral Haemorrhage Patients: Preliminary Study

Abstract: Objectives Spontaneous intracerebral hemorrhage (ICH) accounts for 10 to 20% of all types of stroke and is associated with high mortality and morbidity rates. Neuroinflammation caused by intracerebral blood includes resident microglia activation, infiltration of systemic immune cells, and production of cytokines, chemokines, extracellular proteases, and reactive oxygen species. Despite several findings demonstrating that an immature granulocyte (IG) count can be a prognostic indicator as an inflammatory parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The IG count is less known among physicians, but it is a simple haemogram parameter. Several studies have recently suggested that the IG count can be used to predict both the short- and long-term mortality associated with many diseases [ 12 , 13 ] . The present study has shown that the IG count is an independent risk factor that can be used to predict the prognosis in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IG count is less known among physicians, but it is a simple haemogram parameter. Several studies have recently suggested that the IG count can be used to predict both the short- and long-term mortality associated with many diseases [ 12 , 13 ] . The present study has shown that the IG count is an independent risk factor that can be used to predict the prognosis in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and trauma are known to lead to the occurrence of circulating immature cells that normally should not be present in the peripheral blood. Therefore, the diagnostic and prognostic values of circulating immature cells in sepsis, trauma, and gastrointestinal system diseases have been discussed in many studies [ 12 , 20 , 21 ] . Krishnan et al [ 22 ] reported that the IG count was an effective marker in predicting the severity of the infection and determining the need for early intervention in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it does not require an extra effort, cost and time. Several recent studies have shown that IG can be used to predict short-term mortality [38,39]. In a recent study, it was shown that IG number predicts mortality in upper gastrointestinal system diseases with a cut-off value of 0.95 with a sensitivity of 66.7% and a specificity of 75.7% [11].…”
Section: !"#$%Andf(and)*gand-%3-%//*0and0and/4*-7>7%-+and+*-7"$7?and0...mentioning
confidence: 99%
“…Moreover, in one study, IG was associated with 30-day mortality in acute ischemic stroke (5). However, there is only one study on IG in the literature to predict mortality in patients with SICH, and the relationship between 30-day mortality and IG has been investigated (6). Therefore, in this study, we aimed to investigate the role of IG obtained at admission in predicting in-hospital mortality in patients with SICH.…”
Section: Introductionmentioning
confidence: 98%